1996
DOI: 10.1111/j.1532-5415.1996.tb01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Precedes Dementia in Community‐Dwelling Older Adults

Abstract: Weight loss precedes mild to moderate dementia; early weight loss is, therefore, unlikely to be a consequence of AD patients being unable or unwilling to eat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
173
2
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(198 citation statements)
references
References 32 publications
18
173
2
5
Order By: Relevance
“…Previous studies have shown that higher midlife BMI increases risk for the clinical diagnosis of AD (28)(29)(30), but this effect is diminished or even reversed in latelife (29)(30)(31)(32)(33). A similar pattern is evident in the ex vivo literature.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have shown that higher midlife BMI increases risk for the clinical diagnosis of AD (28)(29)(30), but this effect is diminished or even reversed in latelife (29)(30)(31)(32)(33). A similar pattern is evident in the ex vivo literature.…”
Section: Discussionsupporting
confidence: 65%
“…As noted previously, patients with AD have been found to have lower serum leptin levels compared to controls, independent of BMI (Power et al, 2001). Interestingly, in a 20-year prospective study of 299 community-dwelling older adults, Barrett-Connor et al (1998) found that weight loss precedes mild and moderate dementia, suggesting that early weight loss is unlikely to be a consequence of AD itself, and that AD may be linked to underlying metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 68%
“…In case-controlled studies, patients with AD have lower leptin levels than controls, also independent of body mass index (Power et al, 2001). Weight loss is a common feature of AD, and is found to occur before the onset of dementia (Barrett-Connor et al, 1998), suggesting an underlying metabolic abnormality in the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 96%
“…Weight loss among older people, often due to conditions such as cancer and heart disease, has been associated with increased risks of disability and mortality (Galanos et al, 1994). Weight loss precedes mild and moderate dementia (Barrett-Connor et al, 1996). However, in our longitudinal study height and weight were measured at baseline, before the decline.…”
Section: Discussionmentioning
confidence: 86%